Detection rate of breast malignancy of needle localization biopsy of breast microcalcification - Kian-Hwee Chong; Kuo-Feng Huang; Hsiu-Wen Kuo; I-Shiang Tzeng; Jia-Hui Chen (Tzu Chi Medical Journal)
Objective: The current study aimed to retrospectively assess the cancer detection rate of needle localization biopsy of breast microcalcifications undetectable on sonography. Materials and Methods: Patients who underwent mammography-guided needle localization biopsy of breast microcalcifications undetectable on sonography from January 2005 to December 2017 were included in the study. Patients with incomplete medical records were excluded from the study. Patient mammograms were categorized using the Breast Imaging-Reporting and Data System (BI-RADS) assessment criteria. The percentages of benign and malignant lesions were determined by pathological examination of surgically recovered specimens. Correlation between preoperative imaging assessment and final diagnosis was investigated, and the complications associated with the procedures were recorded. Results: A total of 301 needle-localized biopsies were performed under mammographic guidance. The mean age of the patients was 58.18 ± 7.73 years. The overall ductal carcinoma in situ (DCIS) and cancer detection rate was 23.3%. The proportion of patients with BI-RADS 0 category and undergoing second mammography was higher in the DCIS and cancer group. A total of 227 patients did not undergo second mammography. Of these patients, 70 demonstrated BI-RADS 4 category, 34 were diagnosed with DCIS, and 5 were diagnosed with breast cancer during subsequent follow-up. Conclusion: Needle-localized excision of microcalcifications undetectable on sonography has high detection rate for early stage of breast cancer with low risk of associated complications. Regular mammography is a satisfactory follow-up tool for female patients with microcalcifications in the breasts. Additional studies should be performed to compare between needle-localized excision and vacuum-assisted breast biopsy.